Comorbidities of Maladaptive Daydreaming (MD): A Systematic Review - Aslam, Muhammad Safi; Khaliq, Faiza Abdul; Seher, Ushna; Nashee, Qudsia; Tasleem, Amber; Mehmood, Haziq (Applied Psychology Review, 2025)
Maladaptive Daydreaming (MD) is characterized by imaginary and striking thoughts which obstruct everyday functioning. It is associated with multiple mental health conditions. The objective of the current study is to provide a systematic review of the relationship between maladaptive daydreaming and other mental health disorders. Three databases (Science Direct, PubMed, PsycINFO) were undertaken to identify studies measuring comorbidities of maladaptive daydreaming. Ten studies were identified for inclusion. Cross sectional studies were included which justified the sample. This systematic review highlights the prevalence of comorbid mental health conditions among individuals with maladaptive daydreaming (anxiety, depression, schizophrenia, attention deficit hyperactivity disorder and obsessive-compulsive disorder). This review was pre-registered on PROSPERO as (CRD42024548037).